Sustainable development of the rural economy - Magda, Sándor; Magda , Róbert; Marselek, Sándor (Applied Studies in Agribusiness and Commerce, 2009)
This paper seeks to provide an overview of those economic social and enviromental issues which could be relevant for sustainable development of the rural economy. Rural development is of great significance for the future of both the EU and Hungary. We must reduce migration, create new jobs and focus on sustainability and the principles and goals of environmental protection and nature conservation. Rural economy is a complex and dynamic system, and agriculture should be treated as a part of it.The development of rural settlements and their infrastructure, the manifold exploitation of the agroecological potential, the rationalization of farming remain, extremely important components of rural development.